1987
DOI: 10.1002/ajim.4700110409
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of skin cancer in the tire and rubber manufacturing industry

Abstract: A case-control study was conducted in the tire and rubber manufacturing industry to examine the association of squamous cell carcinoma of the skin with rubber manufacturing materials presumed to be contaminated by polycyclic aromatic hydrocarbons. Sixty-five cases were compared to 254 matched controls for exposure to carbon black, extender oils, lubricating oils, rubber solvents, and rubber stock. Both magnitude and duration of exposure were compared using data from company personnel records. Rubber stock and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Decreased risks of this cancer form have been reported earlier [Sathiakumar et al, 1998;Straughan and Sorahan, 2000] but also a positive association between work in the rubber industry and skin cancer has been reported [Kogevinas et al, 1998] and this risk has in one study been associated with exposure to rubber stock and lubricating oils [Bourguet et al, 1987].…”
Section: Discussionmentioning
confidence: 90%
“…Decreased risks of this cancer form have been reported earlier [Sathiakumar et al, 1998;Straughan and Sorahan, 2000] but also a positive association between work in the rubber industry and skin cancer has been reported [Kogevinas et al, 1998] and this risk has in one study been associated with exposure to rubber stock and lubricating oils [Bourguet et al, 1987].…”
Section: Discussionmentioning
confidence: 90%
“…Only coal dust was associated with an elevated risk of BCC [6]. Further, an elevated SCC risk was detected in a small case-control study of workers in the tire and rubber manufacturing industry (65 SCC cases and 254 controls) who were exposed to rubber materials that may have contained PAHs [11]. Our findings of elevated BCC risk among truck drivers, roofers, and men employed at garages and service stations are consistent with occupational PAH exposure as a possible contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Occupations associated with a statistically significant elevation in BCC or SCC risk or a non-significant increase with a relative risk estimate ‡1.3 were identified as a priori high-risk occupations. Occupations that met our criteria as a priori high-risk for men included roofers and highway maintenance/road workers [11] for both BCC and SCC (or for KC of unspecified histology); carpenters and joiners [9] for BCC only; and wood impregnators for SCC only [13]. If an occupation was identified as high-risk for BCC or SCC only, we included it in the a priori analysis for both BCC and SCC.…”
Section: Occupational Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include unpublished data and studies reported only as abstracts. We identified 12 cohort studies from nine countries examining distinct populations of workers in the rubber industry [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] ; seven nested casecontrol studies in this industry [34][35][36][37][38][39][40] ; 48 distinct community based case-control studies from 16 countries that used questionnaire data and reported risks for employment in the rubber industry ; and finally, 23 studies based on administrative data -such as death certificates, cancer registration, or linkage between census and cancer registry-that presented results by industry or occupation pertinent to assess the risk of cancer among rubber workers. Some of the studies reviewed are updates or more specific investigations of previously reported cohorts.…”
Section: Methodsmentioning
confidence: 99%